The use of lossless compression in the process of post-filtration smoothing of an ECG distorted by high muscle noise - Кривенко, С. А.; Pulavskyi, A. A.; Kryvenko, L. S.; Posokhov, M. F.; Krivenko, S. S. (IEEE, 2020)
The electrocardiogram (ECG) of the first lead, obtained using portable signal collection tools is noise sensitive. One of the most common and poorly filterable types of noise is muscle artefact. As a result of the simulation, a criterion was found that identifies situations in which the use of kernel-based ECG smoothing after the filtering stage is relevant. This criterion is based on the difference in compression coefficients of the ECG smoothed after filtering and filtered ECG. The use of post-filtering smoothing is recommended if this difference is greater than zero. In this case, post-filtering smoothing improves signal quality in terms of mean-square error. The correctness of the criterion was confirmed on real ECG results (MIT-BIH Arrhythmia Database), distorted by real muscle artefact (MIT-BIH Noise Stress Test Database).
Keywords: electrocardiography; filtering theory; medical signal processing